The Effectiveness of Health Education on Knowledge of Danger Signs of Childbirth in Pregnant Women in the Third Trimester - Suriyanti Laba; Rani Safitri (Institut Nalanda, 2024)
Pregnancy, childbirth, and the postpartum period are vulnerable phases for mothers, so readiness in recognizing danger signs of labor is crucial for the safety of the mother and fetus. This study aims to determine the effectiveness of health education in improving pregnant women's knowledge regarding danger signs of labor in the third trimester. The study used a quantitative pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 30 pregnant women in the third trimester who were selected purposively. The health education intervention was provided through group counseling with visual media and guided discussions. Knowledge measurements were conducted before (pretest) and one week after the intervention (posttest) using a valid and reliable structured questionnaire. The results showed a significant increase in maternal knowledge, with the average score increasing from 48.3 to 72.7. The proportion of mothers with good knowledge increased from 6.7 % to 56.7%. In addition, there was a significant positive relationship between the level of posttest knowledge and maternal compliance with childbirth recommendations (p = 0.028). This study confirms that structured, interactive, and family-involved health education effectively improves pregnant women's understanding and behavior in facing the risks of childbirth, thus potentially reducing childbirth complications and supporting the safety of the mother and fetus.